2008
DOI: 10.1002/jpln.200625047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of leaching and runoff losses of selenium from seleniferous soils through simulated rainfall

Abstract: Experiments were conducted to study drainage and runoff losses of selenium (Se) from two seleniferous soils (from Simbly containing total Se 850 lg [kg soil] ±1 and from Barwa containing 1310 lg [kg soil] ±1 ) under simulated rainfall (250±260 mm in three rainstorms) conditions. Rainfall intensities ranged from 56 to 120 mm h ±1 with uniformity coefficients ranging from 70.6% to 84.2%. Selenium lost through drainage (sum of drainage from initially saturated soil for 24 h and through dry and wet runs) was 0.15%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 25 publications
3
14
0
Order By: Relevance
“…The map of study area in Punjab can be found in a report by Dhillon and Dhillon [18]. Total rainfall in that area varies from 631 to 1325 mm a −1 and about 80% of the yearly rainfall of approximately 1000 mm occurs in the rainy season, mainly from July to September [24,29]. The soils of the area are mostly loamy and alkaline in reaction and are considered to be formed from the alluvium deposited by Indus rivers system [18].…”
Section: Study Areamentioning
confidence: 98%
See 1 more Smart Citation
“…The map of study area in Punjab can be found in a report by Dhillon and Dhillon [18]. Total rainfall in that area varies from 631 to 1325 mm a −1 and about 80% of the yearly rainfall of approximately 1000 mm occurs in the rainy season, mainly from July to September [24,29]. The soils of the area are mostly loamy and alkaline in reaction and are considered to be formed from the alluvium deposited by Indus rivers system [18].…”
Section: Study Areamentioning
confidence: 98%
“…The cause of high Se concentrations in the groundwater of this area is still unclear. It was suggested [24,29] that high dissolved Se concentrations in the groundwater could be present due to leaching of Se from seleniferous top soils by rainfall and long-term drainage. In our study, the degree of leaching, however, which was indicated by the Se content in the soil below 15 cm, is probably not sufficient to explain the extremely high Se concentrations in the groundwater at a depth of 76 m. The observed concentrations by far exceeded the Se limits prescribed by the WHO [32].…”
Section: Groundwater Qualitymentioning
confidence: 99%
“…Leaching of selenium species from soil to groundwater is another component of selenium hydrological transport. However, processes governing this leaching are poorly understood, due to the heterogeneity of the water/rocks, soils and sediment interfaces (Dhillon et al 2008). Mean residence time of selenium in the deep ocean is about 1,100 years, i.e., is of the order of water residence time (Ihnat 1989).…”
Section: Isotopes and Radioactivitymentioning
confidence: 99%
“…Soil Se concentrations range from 0.25 to 6.8 mg kg −1 with a mean value of 3.6 mg kg −1 . 16,17 A 2004 study 18 showed that the dietary intake of Se is greater than 600 μg Se day −1 in this region in excess of the recommended WHO limit. 3 Analysis of human hairs and nails revealed 6 to 9 times higher Se contents compared to background levels.…”
Section: ■ Introductionmentioning
confidence: 97%